Inferring the role of pit membranes in solute transport from solute exclusion studies in living conifer stems. (5th February 2020) - Yang, Dongmei; Wei, Kailu; Li, Junhui; Peng, Guoquan; Tyree, Melvin T
Abstract : Lignified cell walls appear to be impermeable to solutes with molecular weight >300, so ray cell to xylem vessel transport is restricted to unlignified pit membranes. Abstract: The functional role of pits between living and dead cells has been inferred from anatomical studies but amassing physiological evidence has been challenging. Centrifugation methods were used to strip water from xylem conduits, permitting a more quantitative gravimetric determination of the water and solid contents of cell walls than is possible by more traditional methods. Quantitative anatomical evidence was used to evaluate the water volume in xylem conduits and the water content of living cells. Quantitative perfusion of stems with polyethylene glycol of different molecular weight was used to determine the solute-free space. We measured the portioning of water and solute-free space among anatomical components in stems and demonstrated that lignin impeded the free movement of solutes with molecular weight >300. Hence, movement of large solutes from living cells to xylem conduits is necessarily confined to pit structures that permit transmembrane solute transport via primary walls without lignin. The functional role of pits was additionally indicated by combining data in this paper with previous studies of unusual osmotic relationships in woody species that lack pits between dead wood fibers and vessels. The absence of pits, combined with the evidence of exclusion of solutes of molecular weight >300, explains the unexpected osmotic properties.